Karakteristik Campuran AC-BASE yang Menggunakan Agregat Sungai Seriti Kabupaten Luwu - Fretty Sumbung Parerung; Robert Mangontan; Alpius (Paulus Civil Engineering Journal, 2022)
The purpose of this study was to determine the characteristics of the AC-Base mixture using aggregate from the Seriti River, Luwu Regency. The method used in this research is the Conventional Marshall Method to test the characteristics of the mixture and Marshall Immertion to determine the resistance of the mixture to weather and climate. The test results of Aggregate Characteristics from the Seriti River meet the requirements of the 2018 Bina Marga Specification to be used as an AC-Base Mixture with a combination of 60/70 penetration Asphalt and cement filler. The characteristics of the mixture with the composition of the mixture of coarse aggregate 53.21%, fine aggregate 36.75%, filler 4.54% and asphalt content of 4.5% to 6.5% all variables of the characteristics of the mixture meet the requirements. The results of the Marshall Residual Stability test, the AC-base mixture using Aggregate from the Seriti River has good resistance to weather and immersion in water for 24 hours.